Analysis of Learning Design for Merdeka Belajar Curriculum in PAI Subjects in Class X SMA Negeri Colamadu - Jermanda Ridwan Kurniaji; Wildan Shohib, Muhammad (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
The concept of "Free Learning Education" was coined by Nadiem Makarim as Minister of Education and Culture delivered during a speech at the 2019 National Teacher's Day (HGN) event. Islamic education in its process uses cognitive, affective, and psychomotor abilities. This study aims to describe the learning design of the independent curriculum for Islamic religious education (PAI) subjects in class X of Colomadu State High School. This research uses a qualitative research design that analyzes microsite-based content, specifically using the analysis of the studied documentation model, including text, images, and interview results. The researcher chose informants who could provide accurate and precise information data, namely the principal and PAI teacher. The data collection techniques used were observation, interview, and documentation. The analysis technique uses the Miles and Huberman model, namely: Data condensation, data presentation, and data verification, and conclusion. Learning design in PAI subjects in class X is based on the independent curriculum using the s.id website created by the teacher, where all learning components are in it starting from pdf books, powerpoint materials, learning videos, daily test questions, practice questions, recapitulation of grades and attendance. Teachers and students agree at the beginning of the year regarding the division of chapters in each semester.